Effects of hormonal and oocyte activation treatments on in vitro embryo development and interspecies hybridization of bovidar embryos following intracytoplasmic sperm injection - Dashtizad, Mojtaba (2011)
In countries in the tropics such as Malaysia, local cattle are not suitable for the feedlot production system because of their poor meat production performance. Therefore, hybridization of domestic cattle with local wild bovids (Bos gaurus hubbacki and Bos javanicus) which are able to thrive very well in the tropics and at the same time develop a large muscular body and sturdy limbs may be an alternative way to improve livestock production system in Malaysia. In vitro embryo production (IVEP) technique plays a crucial role to manage hybridization and therefore may improve the desirable characteristics of livestock. Although IVEP techniques have received great attention in recent years, the rate of transferable blastocysts is quite low. In the present study, to improve the yield of in vitro produced bovine embryos, the effect of different concentrations of insulin and ghrelin hormones on in vitro development of bovine oocytes was evaluated. Insulin at 10 μg/ml significantly improved the proportion of immature bovine oocytes that reached the metaphase II stage. Furthermore, addition of 10 μg/ml insulin into the culture medium showed a positive effect on bovine embryo development until the morula stage. It was also found that supplementation with 50 ng/ml ghrelin in maturation and culture media enhanced nuclear maturation and blastocyst formation rates, respectively. Although inclusion of 50 ng/ml ghrelin in the culture medium strikingly increased the population of inner cell mass (ICM), trophoectoderm (TE) and total cell number cells of bovine blastocysts, no significant difference was detected in ratio of ICM: total cell number per blastocysts between the different treatment groups compared to the control. In order to improve the in vitro bovine embryo development following intracytoplasmic sperm injection (ICSI), a variety of single and combined artificial oocyte activation treatments were assessed. Data analysis showed that single artificial oocyte activation by strontium chloride (20 mM) and combination of strontium chloride followed by ethanol (7%) significantly increased the cleavage rate and in vitro bovine embryo development (p<0.05) following ICSI. However, no significant difference was detected between treatments regarding the quality of the blastocysts evaluated by differential staining of ICM and TE cells. Modified maturation and culture solutions and artificial oocyte activation (AOA) methods resulted from the present study were applied to assess the possibility and efficiency of advanced assisted reproductive techniques on in vitro production of hybrid bovine embryos. Furthermore, the effects of different diameters of the sperm injection needle on in vitro development of bovine embryos were also evaluated. The results indicated that frozen-thawed Bos gaurus hubbacki and Bos javanicus sperm were able to fertilize in vitro matured bovine oocytes and produced interspecies hybrid embryos following both in vitro fertilization (IVF) and ICSI methods at acceptable rates. In addition, the inner diameter of the injection pipette had significant effects on the in vitro production of hybrid embryos. In conclusion, the in vitro mass production of hybrid embryos that were successfully achieved in the present study can be considered as the first step to introduce a novel source of meat for the future.